Exploring the factors that drive luxury tourism : sub-brand by Lapland Safaris case - Andreu Simola, Marc (2023)
The thesis project attempted to understand motivations, preferences, and behaviours of luxury tourism customers. Analyse the main factors that drives luxury customers to develop a luxury sub-brand under Lapland Safaris in Lapland. Various resources related to luxury tourism segment have been studied, as well as sustainability in luxury tourism to give a solid background in the theorical section. The commissioner of this thesis was Lapland Safaris Rovaniemi, founded in 1982 is one of the mayor safari companies in Arctic Europe. The final objective of the thesis was to define the potential of Lapland Safaris entering the luxury market, showing the potential of a growing market and how to match the expectations. Qualitative methodology was the main approach used in the thesis based on interview method with luxury tourism’s experts in Lapland and worldwide, other method used was mystery shopper, used to understand how luxury companies in Lapland approach their potential clients. According to the results, defining luxury tourism was a challenge as the variety and the spectrum inside the segment is large. Every customer is different and close collaboration and communication is required to understand the client and match their expectations. Luxury travellers need unique and customized experiences, high-quality services, use effective of time, authenticity and sustainable products. Lapland is itself a luxury tourism destination for its nature and unique attractiveness but improvement in service is needed to success with luxury travellers. Lapland Safaris tied all the elements to create a luxury sub-brand to succeed in that market, as being an experienced and trustful brand are some of the main requirements for luxury customers, but that can cannibalize other already successful products. Further research is needed to plan the new sub-brand; however, the thesis gives an overall overview about the target market motivations, preferences, and behaviours.